Improving the Ability to Read and Write the Qur'an: A Case Study of the Effectiveness of the Qur'anic Education Center in Kangkung Village, Kangkung District - Risma Sintiya; Pramita Khanifatul; Ikhlas Khadaffy; Aisya Dhefi; Metana Yudha; Sinta Ayu; Herxi Thovan (Universitas Palangka Raya, 2024)
Religious education is the basic education that children need and has a direct impact on their behavior and development. And child development. Religious education in children is the beginning of identity formation. Children who receive information about the Quran since childhood will grow up to be a good and religious person. Learning to read and write the Quran as a foundation for learning the Quran from an early age will create good habits and instill a sense of love in children, their hearts and minds. This research uses a field study with a descriptive qualitative method with data collection techniques in the form of direct observation in the field. Nonetheless, this study also found some challenges, such as limited teaching time and variations in learners' initial ability levels. The findings suggest the need to improve the quality of training for TPQ teachers and develop a curriculum that is more adaptive to learners' needs. The results of this study show that the Qur'anic Education Center (TPQ) has implications in improving children's religious values